Compaction and CBR Characteristics of Sandy Clay Stabilised with Fibre-Mixed Binder - L. Tsai, K.; M. Chan, C.; C. Tan, P. (International Journal of Engineering and Technology, 2019)
Soil chemical stabilization is an effective yet comparatively economical ground improvement method which involves injecting or blending a binder into the existing soil to enhance the geotechnical properties (e.g. strength and stiffness) for load-bearing purposes. The technique is especially beneficial for road construction works on clayey soil of limited load-bearing capacity such as rural roads. It required thick road base is critical to ensure long-term stability and performance. An endeavour is therefore undertaken to examine the effectiveness of a proprietary fibre-mixed binder in stabilizing soils (sandy clay) nature to serve as road base material. Kaolin was mixed with sand as the base soil at ratios of 0, 25 and 50% sand addition. The fibre-mixed binder was added at dosages of 1.5, 2.5 and 3.5% as recommended by the proprietor. Standard compaction test was first carried out to determine the optimum water content for each kaolin-sand mix. Then left to cure for 1, 3, 7 and 28 days before subjected to the California Bearing Ratio (CBR) test. From the test results, it was found that 2.5% binder addition was sufficient to attain the minimum CBR requirement of 30% for supporting a conventional flexible pavement, as per JKR standard. However, the 100% clay sample required higher binder dosages. Clearly sand particles in the soil contributed to the formation of skeletal scaffolding of the soil matrix, bound and supported by the fibre-mixed binder for enhanced strength properties. This was evident in the compaction test where 50% sand addition reduced the optimum water content by almost half compared to the 100% clay. Moreover 3-day curing could adequately strengthen all samples to attain the minimum CBR requirement (JKR standard), irrespective of the binder dosage used. In conclusion, it could effectively strengthen sandy clay soils within 3 days with dosages as low as 2.5%.Â Â